Unmasking the Hidden Threat: Anorectal Lesion Revealed as Malignant Melanoma in a Resected Rectal Polyp - Padmakar Bardapurkar; Mangesh Londhe; Sushama G. Gurwale; Pranjali Nibe; Prachi Chouhan (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Melanoma is a malignant neoplasm arising from melanocytes, primarily affecting the skin. Anorectal mucosal melanoma (ARMM) is an exceedingly rare and aggressive cancer with a poor prognosis. We present a case of a middle aged caucasian male patient with a rectal polyp, bleeding, and discomfort during defecation. A per rectal examination revealed a protruding mass, leading to a diagnosis of a pedunculated rectal mass. Imaging studies confirmed a large mass along the anal canal. The mass was surgically resected, and histopathological examination revealed neoplastic cells consistent with malignant melanoma. Immunohistochemical marker studies confirmed the diagnosis. ARMM is often misdiagnosed due to its rarity and nonspecific symptoms, leading to delayed diagnosis and poor outcomes. Computed tomography (CT) scans aid in assessing disease extent, while immunohistochemical markers assist in confirming the diagnosis. Wide local excision is the mainstay of treatment, although its impact on prognosis is limited due to the systemic nature of the disease. Lymph node dissection may be necessary in specific cases. Further research is required to enhance understanding and establish standardized management approaches for ARMM.